Electro-chemo-mechanical properties in nanostructured Ca-doped ceria (CDC) by field assisted sintering. (October 2020) - Kabir, Ahsanul; Zhang, Haiwu; Colding-Jørgensen, Sofie; Santucci, Simone; Molin, Sebastian; Esposito, Vincenzo
Abstract: Recent investigations have shown that highly oxygen defective cerium oxides generate non-classical electrostriction that is superior to lead-based ferroelectrics. In this work, we report the effect of field-assisted spark plasma sintering (SPS) on electro-chemo-mechanical properties of calcium doped ceria (CDC). Nanometric powders of Ca . 10 nm are rapidly consolidated to form polycrystalline nanostructures with a high degree of crystalline disorder. Remarkably, the resultant material demonstrates a large electromechanical strain without a frequency-related relaxation effect. We conclude that electromechanical activity in CDC materials strictly depends on the Ca 2+ - V o ¨ interaction, while disorder at the crystalline boundaries has a minor effect. Graphical abstract: Image, graphical abstract